A Metal‐Free Electrode: From Biomass‐Derived Carbon to Hydrogen. Issue 16 (10th June 2020) - Ding, Yuxiao; Greiner, Mark; Schlögl, Robert; Heumann, Saskia
Abstract: Hydrogen is the emission‐free fuel of the future if produced from non‐fossil sources. Biomass gasification or electrolysis of water are possible clean routes. For a global application, the material solution for the electrodes must be sustainable, scalable, and relatively inexpensive compared to the current precious metal‐based electrodes. A key requirement to sustainable and green energy systems is that all harmful or rare resources utilized in the process must be part of a closed material cycle. Here, a carbon‐based electrode for hydrogen production is presented that can be part of a closed material cycle if produced from biomass. Continuous hydrogen production takes place at the cathode through catalytic water splitting during the oxygen evolution reaction (OER), while intentionally allowing the decomposition of the electrode into CO2 analogous to the process of natural biomass decomposition. This strategy of a sacrificial electrode could provide a scalable and low‐cost material solution for hydrogen production from renewable energy sources. The theoretical and technical feasibility of using carbon to produce hydrogen is demonstrated, and it is shown that chemical modification can further improve the performance characteristics towards the catalytic process. Combined with renewable energy derived electricity, this idea offers a real option for future energy systems. Abstract : Make a sacrifice : Hydrogen production by electrolysis requires sustainable, scalable, and relatively inexpensive electrodes. Carbon‐based electrodes obtained from waste biomass meet these requirements. Not only the theoretical but also the chemical and technical feasibilities are discussed and experimentally demonstrated. The use of sacrificial carbon electrodes from biomass, operated with renewable energies, reveals a real solution for future energy systems.